BUZZ GROUP-BASED STRATEGY IN EFL READING CLASSROOM - Juang Kurniawan Syahruzah (Universitas PGRI Yogyakarta, 2017)
The intention of this study is to describe the effectiveness of buzz group in EFL reading classroom of English Department students of PGRI University. The comprehension analysis is intended by comparing the answer of EFL reading classroom students in reading exercises. In order to sequence the reading comprehension of the EFL reading classroom the pre-test and post-test of reading exercises are measured. The experiment of reading comprehension includes the recruitment of 40 students of EFL reading classroom, the training, and exercising of reading text in reading exercises. These students are all first-year female teacher training students at PBI-UPY and aged between 17 and 23. The measurement is compare with pre-test and post-test of reading exercises. Standard measurement is comparison of students answer in pre-test and post-test of reading exercises.